Pengaruh Komunikasi Internal, Kompensasi Kerja dan Lingkungan Kerja Terhadap Kepuasan Kerja Karyawan Pada PT. Kimia Farma Plant Semarang - Danang Indra Putranto; Sri Suryoko; Handoyo Djoko Waloejo (Universitas Diponegoro, 2013)
Internal communication, labor compensation, and labor environment are the supporting factors in achieving higher labor satisfaction. When internal communication, labor compensation, and labor environment in a company are considered to be good, the rate of job satisfaction will be high so that the goal of a company could be achieved. The objective of this study is to investigate that there is an effect from internal communication, labor compensation, and labor environment toward job satisfaction In PT Kimia Farma Plant Semarang.The type of this study is explanatory research. The hypothesis used is internal communication (x1), labor compensation (x2), and labor environments (x3) have significant effect toward job satisfaction (y). The technique of data collection used questionnaire, interview, and literature study. The amount of respondents is 95 and all populations member could be made as respondents.The techniques of data analysis are validity study, reliability study, simple linear regression analysis and multiple linear regression analysis which is processed by SPSS 17 for Windows. The conclusion of this study is that internal communication the rate is to be good, labor compensation the rate is proper, and labor environment the rate is to be good toward job satisfaction in PT Kimia Farma Plant Semarang. The test result using SPSS showed that internal communication, labor compensation, and labor environments have positive effect high job satisfaction either simultaneously or partially. Suggestion that can be submitted is for the company to improve and increase the workplace condition especially in the production unit so that the employees feel calm and comfortable in the workplace, so as to have loyalty to bring satisfaction in working.